Climate change projections for variables affecting road networks in Europe - Makkonen, Lasse; Ylhäisi, Jussi S.; Törnqvist, Jouko; Dawson, Andrew; Räisänen, Jouni (Taylor & Francis, 2014)
Global climate change will affect road networks during this century. The effects will be different in various parts of the world due to differences in local climate change and in the structure and properties of roads. In this paper, climate change projections are presented for climate variables that are most likely to affect the long-term performance of road networks in Europe. We apply four regional climate simulations up to the year 2100 using two plausible future emission scenarios. The results show that the changing climate will require significant adaptation measures in the near future in order to maintain the operability of the European road network.